(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Waterlogging is an important abiotic factor affecting crop productivity worldwide. Black gram (Vigna mungo L.) is very sensitive to waterlogged conditions. A field experiment was conducted in randomized complete block design to evaluate three black gram genotypes for waterlogging tolerance. Stress was imposed by maintaining the water level above the soil surface for 10 days after 30 days of sowing. Different physiological parameters including chlorophyll (Chl), chlorophyll fluorescence, normalized difference vegetation index (NDVI), sugars, along with the yield per plant and thousand grain weight (TW) were recorded in control and stressed plants. Results showed that NDVI, Chl, chlorophyll fluorescence, sugars, seed yield and TW reduced significantly during stress. Stress susceptibility index (SSI) for grain yield varied from 0.32 to 2.38. Linear correlation study showed that SSI was negatively correlated with NDVI (0.43),Chl (0.68) and TW (0.42) and grain yield (0.96). NDVI and sugars were correlated to TW under stress. IC530491 and IC559933 (SSI < 0.5) were waterlogging tolerant under field conditions. The study concluded that identified black gram lines may be utilized as trait donors in breeding program.